Legal System Governing the War against Terrorism and its Implications for the Victims of Terrorist Attacks - Mehdi Sabooripour,; Ali Chahkandi,; Seyyed Hassan Hashemi,; Mirza Ali Adabi, (International Journal of Psychosocial Rehabilitation, 2020)
Resort to interventions and procedures in conflict with citizenship rights has currently become pervasive under the title of fight against terrorism and, this is while, the UN has repeatedly emphasized on the necessity for observing the citizenship rights in the fights against terrorism (including in the resolution no.219 in the 57th meeting, resolution no.187 in the 58th meeting and resolution no.191 in the 59th meeting by the general assembly as well as resolution no.1624 by the security council). In this article, efforts will be seminally made to recognize the indispensable legal system in the fight against terrorism and, subsequently, investigate some of the procedures that have been adopted during the recent years in terms of the extent to which they are in accordance with the criteria of the corresponding legal system. Since the most frequent measures under the title of the fight against terrorism are being taken by the US, it is natural for most of the materials to be related to this country but references will be also made to the other countries depending on the discussion’s expediencies.